Application of PDCA Method in Improving the Quality of Valve Production - Dian Putrawangsa; Agustinus Caniago; Samuel Aprilio; Thedy Yogasara (Eduvest - Journal of Universal Studies, 2022)
Plastic is one of the most widely used raw materials for a product. Human life cannot be separated from products or equipment made from plastic. Company X often has problems with the quality of the products produced, especially valve products as products that are produced every day. The corrective step used to assist Company X in improving the quality of valve products is the application of the PDCA method. PDCA method consists of the plan, do, check, and act stages. The proposed improvement design was carried out based on the results of data processing and obtained as many as 9 proposed improvements. In the do stage, implementation of the proposed improvements that have been designed is carried out, five proposed improvements can be implemented and the other four in the form of recommendations. Next is the check stage, which is the process of collecting data again on the results of the implementation of the proposed improvement. Based on the results of the check stage, a standardization process was carried out at the act stage to improve the performance of the proposed improvement and the quality of the valve product. Standardization is done by changing or improving the proposed improvements that have been implemented. Research has succeeded in reducing the number of defective valve products with the proportion of defects that were previously 1.16% to 0.57%.